Geological age of the Yunyang dinosaur eggs revealed by in-situ carbonate U-Pb dating and its scientific implications - Chen, Qingmin; Cheng, Xing; Wang, Jian; Zhao, Bi; Zhang, Shukang; Ning, Youfeng; Wang, Gaohong; He, Kaikai; Zhang, Wenshuo; Yu, Dongxiang; Li, Jiangli; Zou, Yarui; et al. (Frontiers in Earth Science, 2025)
The Cretaceous Period, marked by global events such as volcanic activity, oceanic anoxic episodes, and the end-Cretaceous mass extinction, has been extensively studied in marine records. However, terrestrial Cretaceous systems remain understudied except in regions like northeastern China. Dinosaur eggs, abundant in Upper Cretaceous terrestrial strata, provide critical insights into paleoenvironments, climate, and biotic evolution. The Qinglongshan site in Yunyang District, Shiyan, Hubei Province, preserves thousands of semi-exposed, three-dimensionally intact dinosaur eggs with minimal deformation, offering a rare opportunity to study nesting behavior and environmental dynamics. Preliminary studies classified these eggs as Placoolithus tumiaolingensis (Dendroolithidae), but their chronostratigraphic context remains poorly constrained, hindering regional correlations. This study addresses this research gap by applying Laser Ablation Multi-Collector Inductively Coupled Plasma Mass Spectrometer (LA-MC-ICP-MS) U-Pb dating to biogenic calcite samples from egg - bearing horizons, and the test results indicate an depositional age (DA) of 85.91 ± 1.74 Ma. The results aim to establish a robust chronological framework for the Qinglongshan egg assemblage for the first time, enhancing understanding of Late Cretaceous terrestrial ecosystems in China’s interior and their response to global environmental changes. This study underscores the potential of dinosaur egg fossils as proxies for reconstructing the “Cretaceous World” in terrestrial settings.